2022
DOI: 10.3390/cells11203280
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Non-Small-Cell Lung Cancer Patients with Driver Alterations: A New Strategy?

Abstract: For many years, researchers have been trying to develop the most effective ways to fight lung cancer, which is the cause of the largest number of cancer-related deaths among men and women worldwide. The most advanced treatments for nearly all non-small-cell lung cancer (NSCLC) types include immunotherapy with immune checkpoint inhibitors (ICIs), mainly anti-programmed death 1/anti-programmed death ligand 1 monoclonal antibodies (anti-PD-1/PD-L1 mAbs) in monotherapy or in combination with other strategies. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Our results are reinforced by other studies that have reported that BRAF mutations are associated with higher expression of the PD-L1 protein in thyroid cancer, and that increased PD-L1 expression is significantly associated with disease recurrence and poor survival [ 19 , 20 ]. The direct and significant association between BRAF mutations and a higher level of PD-L1 expression in thyroid cancer, as also described in other human cancers, such as NSCLC, is probably due to a relatively higher TMB level [ 21 , 22 ] or the induction of epithelial/mesenchymal (EM) transition with subsequent greater tumor immune evasion, as a consequence of AXL-PI3Kinase-PD-L1 signaling axis activation, a mechanism recently described in head and neck and lung cancer [ 23 , 24 ]. Nonetheless, the presence of higher levels of CD8+ in the tumor microenvironment could be an index of a patient’s better immune response, and, consequently, of the higher PD-L1 expression, indicating the higher intrinsic immune escape capability of the tumor [ 25 ].…”
Section: Discussionmentioning
confidence: 93%
“…Our results are reinforced by other studies that have reported that BRAF mutations are associated with higher expression of the PD-L1 protein in thyroid cancer, and that increased PD-L1 expression is significantly associated with disease recurrence and poor survival [ 19 , 20 ]. The direct and significant association between BRAF mutations and a higher level of PD-L1 expression in thyroid cancer, as also described in other human cancers, such as NSCLC, is probably due to a relatively higher TMB level [ 21 , 22 ] or the induction of epithelial/mesenchymal (EM) transition with subsequent greater tumor immune evasion, as a consequence of AXL-PI3Kinase-PD-L1 signaling axis activation, a mechanism recently described in head and neck and lung cancer [ 23 , 24 ]. Nonetheless, the presence of higher levels of CD8+ in the tumor microenvironment could be an index of a patient’s better immune response, and, consequently, of the higher PD-L1 expression, indicating the higher intrinsic immune escape capability of the tumor [ 25 ].…”
Section: Discussionmentioning
confidence: 93%
“…Sabari et al [25] researched the response to ICIs in a group of 24 NSCLC patients with the MET exon 14 skipping mutation. They reported an ORR of 17% and PFS of 1.9 months [25,26].…”
Section: Discussionmentioning
confidence: 98%
“…Differences in response are probably related to tumor microenvironment (TME) characteristics that are diverse, depending on the alterations occurring. STK11-mutated tumors exhibit lower lymphocyte infiltration and lower PD-L1 expression, compared to TP53-mutated ones [2].…”
Section: The Efficacy Of Immunotherapy and Chemoimmunotherapy In Kras...mentioning
confidence: 89%
“…However, the coexistence of KRAS mutations and mutations in suppressor genes, such as STK11 (Serine/Threonine Kinase 11 also called Liver Kinase B1, LKB1), may result in the lack of response to immunotherapy. Contrarily, the coexistence of mutations in the KRAS and TP53 (tumor protein p53) genes may increase the effectiveness of immunotherapy [2].…”
mentioning
confidence: 99%